Roblems of electronic banking in the context of sanctions ("Journal "U". Economy. Management. Finance.", 2025)
This article discusses the problems of functioning and development of electronic banking in the context of international sanctions. Restrictions on access to foreign software, hardware, and international payment systems create significant difficulties in maintaining the quality of service, ensuring transaction security, and implementing innovative solutions. The purpose of the article is to analyze the impact of sanctions on the quality management system in the field of electronic banking. The object of the research is information technologies and quality management systems in electronic banking under the conditions of sanctions pressure. The main research method is the collection, analysis and systematization of regulatory and legal documentation, industry analytics, scientific publications of domestic and foreign experts devoted to the problems and prospects of electronic banking development in the context of sanctions. The study will identify the main problems hindering the development of electronic banking under the sanctions regime, as well as suggest ways to solve them and strategies for adapting to new economic realities.
Keywords: electronic banking; sanctions; financial restrictions; quality management; information technology; cybersecurity; import substitution; financial stability; payment systems; digital transformation